Establishment of critical zinc, phosphorus: zinc ratio limits in safflower - MURTHY, I Y L N; PADMAVATHI, P (The Indian Journal of Agricultural Sciences, 2011)
Two field experiments were conducted during 2004–05 at DOR-ICRISAT experimental farm on 2 safflower (Carthamus tinctorius L.) genotypes ‘A 1’ and ‘NARI-NH-1’ to establish critical zinc, phosphorus: zinc ratios in Vertisol. Establishment of critical nutrient limits for soil and plant will help in delineating responsive from non responsive soil types/genotypes. The critical zinc and phosphorus: zinc ratio for ‘A-1’ safflower was 25.9 mg/kg and 80.2 and 27.0 mg/kg and 81.0 for ‘NARI-NH1’ at flowering stage. Similarly critical DTPA-zinc in the black soil (Vertisol) in which the genotypes were grown was also determined and was found to be 0.63 mg/kg for ‘A1’ and 0.72 mg/kg for ‘NARI-NH1’.